Caring Stress Management: A Qualitative Study of Strategies Used by Iranian Nurses - Amir Hossein Goudarzian; Elham Navab; Hamid Sharif‐Nia; Rebecca H. Lehto; Alireza Nikbakht Nasrabadi; Omolhoda Kaveh; Sara Alavi; Pouya Farzami (Nursing Open, 2026)
ABSTRACT Aim To explore caring stress management among Iranian nurses. Design A qualitative study using conventional content analysis explored Iranian nurses' experiences with caring stress management. Methods Using purposive sampling, fifteen registered nurses with full‐time positions in high‐acuity clinical units across four public teaching hospitals in Tehran, Iran, participated in individualized semi‐structured interviews. Data were analysed using conventional qualitative content analysis following an established framework. Results Managing caring stress involved a multi‐layered process. Nurses engaged in professional interactions. sought organizational support, focused on enhancing their clinical care knowledge and skills, and utilized rigorous time and care management. Strategies also included establishing effective therapeutic communication, dedicating more time to follow‐up care, practicing psychological care to build self‐confidence, and trying self‐care practices. The ability to manage caring stress was not uniform; with nurses describing significant structural and contextual barriers. Heavy workloads, severe nursing shortages, compressed shift schedules and lack of systematic institutional support frequently disrupted their capacity to consistently implement caring stress management, with some describing episodic severe emotional weariness and ethical dilemmas in isolation. Conclusion The findings suggest that caring stress is a complex, multifaceted phenomenon influenced by a dynamic interaction among individual, professional and organizational factors. Effective caring stress management doesn't rest solely on individualized coping efforts; it is a larger system process that requires an institutional culture that prioritizes the importance of nursing well‐being alongside clinical duties. System‐level challenges, exacerbated by resource constraints, need addressing to bolster nursing resilience, minimize medical errors and sustain the Iranian nursing workforce. Clinical Implications for the Profession Caring stress management is recommended to be integrated into institutional culture. Since nurses are vital stakeholders in patient safety, caring stress may directly or indirectly threaten care quality. A more supportive, resource‐balanced approach could help nurses cope with daily caring demands. Healthcare administrators may consider structured team‐building initiatives, peer support networks and simulation‐based training. Furthermore, nurses could benefit from being offered concrete self‐care provisions independently, such as flexible scheduling, dedicated relaxation spaces and accessible psychological counselling services. Reporting Method The study adhered to EQUATOR guidelines and the COREQ checklist for qualitative studies. Patient or Public Contribution No patient or public contribution.